METODE KETELADANAN GURU TERHADAP KECERDASAN MURID - Abbas, Ngatmin; Nuriana, Mutia Azizah (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Agama Islam Mulia Astuti (STAIMAS) Wonogiri, 2023)
The exemplary method is a method that from the past until now is considered the most interesting to study. The purpose of examining this exemplary method is for character building. Character education is part of the national education system and it is recognized that exemplary teachers will produce intelligent students. The exemplary method is the core of the teaching that was conveyed by the Prophet Muhammad, and from this exemplary he was able to bring about the best generations throughout his history. The approach technique used in this study is (library research), namely research that seeks to focus on analyzing or interpreting written material based on its context. In this case the book Rasulullah the Teacher by Abdul Fattah Abu Ghuddah. The results of the study, Abdul Fattah Abu Ghuddah believes that the exemplary method has a stronger influence on intelligence, makes an impression on the soul, makes it easier to understand. It is more interesting to follow and emulate than the lecture and explanation methods. In determining a method Abdul Fattah Abu Ghuddah makes the Al-Qur'an and hadith as his philosophical foundation. Keywords: Exemplary Method, Rasulullah, Intelligence